Phytochemical studies of Cryptocarya species and their bioactivities / Wan Nurul Nazneem Wan Othman - Wan Nurul Nazneem, Wan Othman (2017)
Phytochemical analysis and bioactivity studies on three species of Lauraceae, Cryptocarya densiflora Blume, Cryptocarya infectoria Miq. and Cryptocarya griffithiana Wight have been conducted. A total of twenty alkaloids were successfully isolated and purified using several chromatographic techniques such as column chromatography (CC), thin layer chromatography (TLC) and preparative thin layer chromatography (PTLC). The structural elucidations were established through several spectroscopic methods; notably 1D NMR (1H, 13C and DEPT), 2D NMR (COSY, NOESY, HSQC and HMBC), MS, UV, IR, as well as by comparison with those reported in the literature. Investigation of the leaves of C. densiflora yielded fourteen alkaloids in which four of them are new. The new alkaloids were named as prodensiflorin A 126, prodensiflorin B 127, (-)-densiindolizidine 128 and (-)-desmethylsecoantofine-N-oxide 131, while the known alkaloids were characterized as (-)-antofine 6, (-)-isocaryachine 61, (+)-reticuline 76, (+)-laurotetanine 86, (+)-N-methyllaurotetanine 87, (+)-nornantenine 123, dicentrinone 124, (+)-oridine 125, (-)-desmethylsecoantofine 130 and crychine 134. Isolation works on the bark of C. infectoria has resulted six known alkaloids; (+)-Nmethylisococlaurine 14, atherosperminine 15, (+)-reticuline 76, (+)-laurotetanine 86, (+)- N-methyllaurotetanine 87 and argentinine 135, meanwhile the leaves afforded two compounds, argentinine 135 and liriodenine 136. Extensive chromatographic purification on the bark of C. griffithiana has led to the isolation of six known alkaloids; 2- hydroxyatherosperminine 13, 2-methoxyatherosperminine 72, (+)-reticuline 76, (+)-Nmethyllaurotetanine 87, (+)-nornantenine 123 and argentinine 135. DPPH inhibitory activity of the four alkaloids from the leaves of C. densiflora was evaluated and compared to ascorbic acid 137, as the positive control. Alkaloid (-)-desmethylsecoantofine 130 exhibited more effective free radical scavenging with an IC50 value of 62.40 ± 0.05 μg/mL followed by (+)-N-methyllaurotetanine 87 with an IC50 value of 130.00 ± 0.07 μg/mL.